(3GJLGgGJ eYGUQIs - (3YOfGf JGjg(B, (3GdfYjejs; (3GdJejejfGQTO aDGO(B, s ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2008)
(3jVe eONd Edi GdJMdjd GdeGdj, GdGJLGgGJ GdJbdjOjI dCOhGJ GdJMdjd GdeGdj GdJMdjd HGSJNOGe GdfSH GdeGdjI , GdGJLGgGJ GdMOjKI aj GdJMdjd GdeGdj , GdeaGgje GdGSGSjI aj GdJNWjW GdeGdj , JNWjW GdJOabGJ GdfbOjI h GdGMJjGLGJ GdeGdjI , GdJNWjW h GdQHMjI , JNWjW eNGWQ GdJOabGJ GdfbOjI (B.s
(3HjHdjhZQGajG(B: (3U(B.375- 382s
Keywords: (3GdGbJUGO GdJMdjdjs; (3GdJNWjWs; (3GdSjGSI GdeGdjIs